Observations of the singly Cabibbo-suppressed decays Ξ c + → p K S 0 $$ Ξ_c^{+}→ pK_S^0 $$ , Ξ c + → Λ π + $$ Ξ_c^{+}→ Λ π^{+} $$ , and Ξ c + → Σ 0 π + $$ Ξ_c^{+}→ Σ^0π^{+} $$ at Belle and Belle II - The Belle and Belle II collaborations; I. Adachi; L. Aggarwal; N. Akopov; M. Alhakami; A. Aloisio; N. Althubiti; N. Anh Ky; D. M. Asner; H. Atmacan; T. Aushev; V. Aushev; et al. (Journal of High Energy Physics)
Abstract Using data samples of 983.0 fb −1 and 427.9 fb −1 accumulated with the Belle and Belle II detectors operating at the KEKB and SuperKEKB asymmetric-energy e + e − colliders, singly Cabibbo-suppressed decays Ξ c + → p K S 0 $$ {\Xi}_c^{+}\to p{K}_S^0 $$ , Ξ c + → Λ π + $$ {\Xi}_c^{+}\to \Lambda {\pi}^{+} $$ , and Ξ c + → Σ 0 π + $$ {\Xi}_c^{+}\to {\Sigma}^0{\pi}^{+} $$ are observed for the first time. The ratios of branching fractions of Ξ c + → p K S 0 $$ {\Xi}_c^{+}\to p{K}_S^0 $$ , Ξ c + → Λ π + $$ {\Xi}_c^{+}\to \Lambda {\pi}^{+} $$ , and Ξ c + → Σ 0 π + $$ {\Xi}_c^{+}\to {\Sigma}^0{\pi}^{+} $$ relative to that of Ξ c + → Ξ − π + π + $$ {\Xi}_c^{+}\to {\Xi}^{-}{\pi}^{+}{\pi}^{+} $$ are measured to be B Ξ c + → p K S 0 B Ξ c + → Ξ − π + π + = 2.47 ± 0.16 ± 0.07 % , B Ξ c + → Λ π + B Ξ c + → Ξ − π + π + = 1.56 ± 0.14 ± 0.09 % , B Ξ c + → Σ 0 π + B Ξ c + → Ξ − π + π + = 4.13 ± 0.26 ± 0.22 % . $$ {\displaystyle \begin{array}{c}\frac{\mathcal{B}\left({\Xi}_c^{+}\to p{K}_S^0\right)}{\mathcal{B}\left({\Xi}_c^{+}\to {\Xi}^{-}{\pi}^{+}{\pi}^{+}\right)}=\left(2.47\pm 0.16\pm 0.07\right)\%,\\ {}\frac{\mathcal{B}\left({\Xi}_c^{+}\to \Lambda {\pi}^{+}\right)}{\mathcal{B}\left({\Xi}_c^{+}\to {\Xi}^{-}{\pi}^{+}{\pi}^{+}\right)}=\left(1.56\pm 0.14\pm 0.09\right)\%,\\ {}\frac{\mathcal{B}\left({\Xi}_c^{+}\to {\Sigma}^0{\pi}^{+}\right)}{\mathcal{B}\left({\Xi}_c^{+}\to {\Xi}^{-}{\pi}^{+}{\pi}^{+}\right)}=\left(4.13\pm 0.26\pm 0.22\right)\%.\end{array}} $$ Multiplying these values by the branching fraction of the normalization channel, B Ξ c + → Ξ − π + π + = 2.9 ± 1.3 % $$ \mathcal{B}\left({\Xi}_c^{+}\to {\Xi}^{-}{\pi}^{+}{\pi}^{+}\right)=\left(2.9\pm 1.3\right)\% $$ , the absolute branching fractions are determined to be B Ξ c + → p K S 0 = 7.16 ± 0.46 ± 0.20 ± 3.21 × 10 − 4 , B Ξ c + → Λ π + = 4.52 ± 0.41 ± 0.26 ± 2.03 × 10 − 4 , B Ξ c + → Σ 0 π + = 1.20 ± 0.08 ± 0.07 ± 0.54 × 10 − 3 . $$ {\displaystyle \begin{array}{c}\mathcal{B}\left({\Xi}_c^{+}\to p{K}_S^0\right)=\left(7.16\pm 0.46\pm 0.20\pm 3.21\right)\times {10}^{-4},\\ {}\mathcal{B}\left({\Xi}_c^{+}\to \Lambda {\pi}^{+}\right)=\left(4.52\pm 0.41\pm 0.26\pm 2.03\right)\times {10}^{-4},\\ {}\mathcal{B}\left({\Xi}_c^{+}\to {\Sigma}^0{\pi}^{+}\right)=\left(1.20\pm 0.08\pm 0.07\pm 0.54\right)\times {10}^{-3}.\end{array}} $$ The first and second uncertainties above are statistical and systematic, respectively, while the third ones arise from the uncertainty in B Ξ c + → Ξ − π + π + $$ \mathcal{B}\left({\Xi}_c^{+}\to {\Xi}^{-}{\pi}^{+}{\pi}^{+}\right) $$ .